The new american desk encyclopedia - Paxson, William C.; Paxson, William C.; Lewis, Norman (United State of America : A Signet Book, 1993)
This authoriative A-to Z guide to people, historial and contemporary events is clearly written, easy -to-date use comprohensive in scope, and completely up-to date. Its extraordinary coverage of almost every aspect of human knowledge and activity makes it the ideal reference volume for home, office or classroom special features inclde.
1. Anthropology 2. Astronomy 3. Business and finance 4. History - law 5. Mathematics 6. Painting 7. Popular culture 8. Religion 9. Techonology
Incluye Census Data
Keywords: ENCICLOPEDIAS Y DICCIONARIOS -; INGLÉS